O3-phase ferro-manganese-nickel-based high-entropy sodium electric layered oxide as well as preparation method and application thereof
By adopting O3 phase iron -manganese nickel -based high -entropy sodium electromotone as the positive electrode material, the problem of poor performance and impedance of O3 phase oxides, and realized high magnification, low impedance and good electrochemical properties. Applicable High -performance application in sodium ion batteries.
Patent Information
- Application Number
- CN202410313073.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-19
- Publication Date
- 2025-01-28
AI Technical Summary
When O3 phase oxide is used as a positive electrode material, its rate performance and impedance are poor, which affects the cycle rate performance and electrochemical performance of sodium ion batteries.
The O3 phase iron -manganese nickel -based high -entropy sodium sodium -shaped oxide is used, and the chemical formula is NA (FEMNNIXYZ) 1/6O2, X, Y, and Z are three types of AL3+, V3+, TI4+, ZR4+, CE4+, SN4+ This material is prepared by solid-phase, solid-gel method or spray drying legal system to form a transition metal layer and alkaline metal ion octopus structure to improve ions and electronic transmission capabilities.
A high magnification and low impedance are achieved, and the circulation multiplier performance and electrochemical performance of sodium ion battery are improved, and the material has good air stability and the cost is relatively low.
Smart Images

Figure CN119381443A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of battery materials, and in particular to an O3-phase iron-manganese-nickel-based high-entropy sodium-electrolyte layered oxide and a preparation method and application thereof. Background Art
[0002] The working principle of sodium-ion batteries is similar to that of lithium-ion batteries, which utilizes the insertion and removal of sodium ions between the positive and negative electrodes to achieve battery charging and discharging. As an important component of sodium-ion batteries, the positive electrode material determines the electrochemical performance of the battery. Developing positive electrode materials with stable structures and fast sodium ion diffusion properties is one of the challenges in obtaining high-performance sodium-ion batteries. The three technical routes for positive electrode materials for sodium-ion batteries, layered oxides, Prussian blue (white) and polyanions, have their own advantages and disadvantages in performance and cost. The layered oxide system has a simple preparation method, high specific capacity and voltage, but poor stability in air.
[0003] In recent years, more and more layered cathode material systems have been developed and have shown good electrochemical performance, which has good application prospects for sodium ion batteries. For example, patent CN104795560B discloses a sodium-rich P2 phase layered oxide material and its preparation method and use. The chemical formula of the material is Na 0.72+δ Ni a Mn b M c O 2+σ , M is specifically Mg 2+ , Zn 2 + , Mn 2+ ,Co 2+ , Al 3+ , Mn 3+ , Fe 3+ ,Co 3+ , V 3+ ,Cr 3+ , Ti 4+ , Zr 4+ , Si 4+ , Sn 4+ , Ru 4+ , Nb 4+ , Mo 4+ One or more of; δ, a, b, c, σ and m satisfy (0.72+δ)+2a+4b+mc=2(2+σ) and a+b+c=1. Patent CN113078298A discloses a sodium magnesium iron manganese based layered oxide material, a preparation method and use. The chemical formula of the material is Na a [Mg b Fe c Mn d ]O 2+β. Among them, a, b, c, d, and β are the molar percentages of the corresponding elements respectively; the relationship between them satisfies b + c + d = 1, and a + 2b + 3c + 4d = 2×(2 + β); where 0.67 ≤ a ≤ 1; 0.083 ≤ b ≤ 0.33; 0.16 ≤ c ≤ 0.67; 0.25 ≤ d ≤ 0.5; -0.02 ≤ β ≤ 0.02. Patent CN104795561B discloses a layered O3-phase nickel-containing oxide cathode material, its preparation method and use. The chemical general formula of the material is Na x A a Ni b Ti c O 2-δ . A is Li + 、Mg 2+ 、B 3+ 、Cu 2+ 、Zn 2+ 、Co 3+ 、Al 3 + 、V 3+ 、Fe 3+ 、Mn 3+ 、Mn 4+ one or more of; the relationship between x, a, b, c, δ and m satisfies x + ma + 2b + 4c = 2(2 - δ), a + b + c = 1; where, 0.75 < x < 1, 0 < a < b < c < δ. The cathode materials of the above patents show high initial Coulomb efficiency and capacity, but neither of them involves the rate performance and impedance of the battery. The rate performance and impedance of the battery are closely related to the ionic conductivity and electronic conductivity of the sodium battery cathode material. Therefore, an ideal solution is needed. Summary of the Invention
[0004] In order to overcome the problems of poor rate performance and impedance of O3-phase oxides used as cathode materials, the present invention provides an O3-phase iron-manganese-nickel-based high-entropy sodium battery layered oxide, its preparation method and application. The layered oxide can provide fast ion transport and electron transport to achieve high rate and low impedance of the battery, thereby improving the cycle rate performance and other electrochemical performances of the sodium ion secondary battery using this material as the cathode material.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: An O3-phase iron-manganese-nickel-based high-entropy sodium battery layered oxide, the chemical general formula of which is: Na(FeMnNiXYZ) 1 / 6 O2, where X, Y, and Z are Al 3+ 、V 3+ 、Ti 4+ , Zr 4+ , Ce 4+ , Sn 4+ three of them.
[0006] Preferably, the structure of the layered oxide is: Fe, Mn, Ni, X, Y and Z form an octahedral structure with the six nearest oxygen atoms, and are arranged side by side to form a transition metal layer, and the alkali metal ion Na + It occupies an octahedral position between every two transition metal layers.
[0007] The present invention also provides a method for preparing the layered oxide material, which is a solid phase method, comprising the following steps: mixing sodium salt and oxides of Fe, Mn, Ni, X, Y, and Z in proportion to form a precursor; after mixing, heat treating at 800 to 1000° C. for 10 to 24 hours; and obtaining the layered oxide.
[0008] The present invention also provides another preparation method of the layered oxide material, which is a sol-gel method, comprising the following steps: dispersing sodium salt and nitrate or sulfate containing nickel, manganese, iron and salt of XYZ in a solvent to obtain a slurry; stirring at 50-100°C, adding an appropriate amount of chelating agent, and evaporating to form a precursor gel; pre-calcining the precursor gel at 200-500°C for 2-3h; and then heat treating at 600-1000°C for 2-24h; grinding the heat-treated precursor powder to obtain the layered oxide.
[0009] The present invention also provides another preparation method of the layered oxide material, which is a spray drying method, comprising the following steps: dispersing sodium salt and nitrate or sulfate containing nickel, manganese, iron and salt of XYZ in an equal molar ratio in a solvent and stirring evenly to form a slurry; spray drying the slurry to obtain a precursor mixture; heat treating the precursor mixture in an air atmosphere at 700 to 1000° C. for 10 to 24 hours to obtain the layered oxide.
[0010] The present invention also provides application of the layered oxide as a positive electrode material.
[0011] The present invention also provides a positive electrode plate, comprising: a current collector, a conductive additive coated on the current collector, a binder and the positive electrode material.
[0012] Preferably, the conductive additive includes: one or more of carbon black, graphite powder, carbon nanotubes, and graphene; the binder includes: a solution of one or more of polyvinylidene fluoride PVDF, polytetrafluoroethylene PTFE, sodium alginate, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR; the current collector includes: one of aluminum foil, nickel mesh, titanium mesh, stainless steel mesh, and nickel foam.
[0013] The present invention also provides a sodium ion battery, including the positive electrode sheet. The sodium ion secondary battery using the layered O3 phase iron-manganese-nickel-based high entropy sodium electric layered positive electrode material of the present invention has a high capacity, a suitable voltage range, a relatively low cost, and a high first-cycle coulomb efficiency, and can be used for large-scale energy storage equipment for solar power generation, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations.
[0014] Therefore, the beneficial effects of the present invention are as follows: (1) The layered oxide of the present invention has an O3 phase layered structure, good air stability, high capacity and suitable voltage range. (2) The preparation is simple, the elements contained are environmentally friendly elements and are highly abundant in the earth's crust, and the manufacturing cost is relatively low. (3) High entropy materials have unique thermal, electrical and mechanical properties, and have excellent ion and electron transport capabilities, which help to achieve high rate and low impedance of the battery, thereby improving the cycle rate performance of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a schematic diagram of the structure of a layered oxide; in the figure: 1. Sodium atoms, 2. Oxygen atoms, 3. Transition metal layer. DETAILED DESCRIPTION
[0016] The technical solution of the present invention is further described below through specific embodiments.
[0017] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art.
[0018] An O3 phase iron-manganese-nickel based high entropy sodium layered oxide with the general chemical formula: Na(FeMnNiXYZ) 1 / 6 O2, X, Y and Z are Al 3+ 、V 3+ 、Ti 4+ , Zr 4+ 、Ce 4+ Sn 4+ The structure of the layered oxide is as follows Figure 1 As shown: Fe, Mn, Ni, X, Y and Z form an octahedral structure with the six nearest oxygen atoms 2, and are arranged edge-to-edge to form a transition metal layer 3. The alkali metal ion Na + 1 is located between every two transition metal layers and occupies an octahedral position.
[0019] The preparation method of the layered oxide adopts one of (1) a solid phase method, (2) a sol-gel method, and (3) a spray drying method, which is specifically as follows: (1) Solid phase method. It includes the following steps: mixing sodium salt and oxides of Fe, Mn, Ni, X, Y, and Z in proportion to form a precursor; after mixing, heat treating at 800 to 1000° C. for 10 to 24 hours; and obtaining the layered oxide.
[0020] The specific steps are: mixing sodium carbonate with a stoichiometric amount of 102 to 108 wt% of the required sodium and manganese dioxide, nickel oxide, iron oxide and / or ferroferric oxide, and XYZ oxide with a required stoichiometric amount in proportion to form a precursor; uniformly mixing the precursors by a ball milling method, or stirring the precursors in a volatile organic solvent and then completely volatilizing the organic solvent to obtain a precursor powder; heat-treating the precursor powder in an air atmosphere at 800 to 1000° C. for 10 to 24 hours to obtain the layered oxide.
[0021] (2) Sol-gel method. It includes the following steps: dispersing sodium salt and nitrate or sulfate containing nickel, manganese, iron and salt of XYZ in a solvent to obtain slurry; stirring at 50-100°C, adding an appropriate amount of chelating agent, and evaporating to form a precursor gel; pre-calcining the precursor gel at 200-500°C for 2-3h; and then heat treating at 600-1000°C for 2-24h; grinding the heat-treated precursor powder to obtain the layered oxide.
[0022] The specific steps are as follows: dissolving one or more of sodium acetate, sodium nitrate, sodium carbonate or sodium sulfate with a stoichiometric amount of 102 to 108 wt% of the required sodium, and nitrates or sulfates containing nickel, manganese and iron and salts of XYZ in equal molar ratios in water or ethanol to form a precursor solution; stirring at 50 to 100° C., adding an appropriate amount of a chelating agent such as citric acid, and evaporating to form a precursor gel; placing the precursor gel in a crucible, pre-calcining for 2 hours in an air atmosphere at 200 to 500° C.; and then heat treating at 600 to 1000° C. for 2 to 24 hours; grinding the heat-treated precursor powder to obtain the layered oxide.
[0023] (3) Spray drying method. The method comprises the following steps: dispersing sodium salt and nitrate or sulfate containing nickel, manganese, iron and salt of XYZ in equal molar ratio in a solvent and stirring them uniformly to form a slurry; spray drying the slurry to obtain a precursor mixture; heat treating the precursor mixture in an air atmosphere at 700 to 1000° C. for 10 to 24 hours to obtain the layered oxide.
[0024] The specific steps are: dispersing one or more of sodium acetate, sodium nitrate, sodium carbonate or sodium sulfate with a stoichiometric amount of 102 to 108 wt% of the required sodium, and nitrates or sulfates containing nickel, manganese, iron and salts of XYZ in equal molar ratios in ethanol or water and stirring evenly to form a slurry; spray-drying the slurry to obtain a precursor mixture; placing the precursor mixture in a muffle furnace and heat-treating it in an air atmosphere at 700 to 1000° C. for 10 to 24 hours to obtain the layered oxide.
[0025] The present invention also provides application of the layered oxide as a positive electrode material.
[0026] The present invention also provides a positive electrode plate, comprising: a current collector, a conductive additive coated on the current collector, a binder and the positive electrode material. The conductive additive comprises: one or more of carbon black, graphite powder, carbon nanotubes, and graphene; the binder comprises: a solution of one or more of polyvinylidene fluoride PVDF, polytetrafluoroethylene PTFE, sodium alginate, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR; the current collector comprises: one of aluminum foil, nickel mesh, titanium mesh, stainless steel mesh, and nickel foam.
[0027] The present invention also provides a sodium ion battery, comprising the positive electrode sheet.
[0028] Example 1 An O3 phase iron-manganese-nickel based high entropy sodium electric layered oxide, the general chemical formula is: Na(FeMnNiAlTiV) 1 / 6 O2.
[0029] The preparation method of the layered oxide adopts a spray drying method, which is specifically as follows: The required sodium stoichiometric amount of 105wt% sodium acetate and nitrates containing nickel, manganese, iron and Al in equal molar ratios are added. 3+ 、V 3+ 、Ti 4+ The salt is dispersed in ethanol and stirred evenly to form a slurry; the slurry is spray-dried to obtain a precursor mixture; the precursor mixture is placed in a muffle furnace and heat-treated in an air atmosphere at 800° C. for 15 hours to obtain the layered oxide Na(FeMnNiAlTiV) 1 / 6 O2.
[0030] The structure of the layered oxide is as follows Figure 1 As shown: Fe, Mn, Ni, Al, Ti, V form an octahedral structure with the six nearest oxygen atoms 2, and are arranged side by side to form a transition metal layer 3. The alkali metal ion Na + 1 is located between every two transition metal layers and occupies an octahedral position.
[0031] Example 2 The difference from Example 1 is that the preparation method of the layered oxide adopts a solid phase method.
[0032] An O3 phase iron-manganese-nickel based high entropy sodium electric layered oxide, the general chemical formula is: Na(FeMnNiAlTiV) 1 / 6 O2.
[0033] The preparation method of the layered oxide is a solid phase method, which is specifically as follows: Na2CO3 (analytical grade) and NiO, MnO2, Al2O3, V2O3 and TiO2 are mixed in a stoichiometric ratio, wherein Na is 2% in excess, and the mixture is ground in an agate mortar for half an hour to obtain a precursor; the precursor material is pressed into a tablet and transferred to a crucible, and heat-treated in an air atmosphere at 1000° C. for 20 hours to obtain the layered oxide Na(FeMnNiAlTiV) 1 / 6 O2, grind and set aside.
[0034] The structure of the layered oxide is: Fe, Mn, Ni, Al, Ti, V and the six nearest oxygen atoms form an octahedral structure and are arranged side by side to form a transition metal layer. + It occupies an octahedral position between every two transition metal layers.
[0035] Example 3 The difference from Example 1 is that the chemical formula of the layered oxide is: Na(FeMnNiAlTiCe) 1 / 6 O2.
[0036] An O3 phase iron-manganese-nickel based high entropy sodium layered oxide with the general chemical formula: Na(FeMnNiAlTiCe) 1 / 6 O2.
[0037] The preparation method of the layered oxide adopts a spray drying method, which is specifically as follows: The required sodium stoichiometric amount of 105wt% sodium acetate and nitrates containing nickel, manganese, iron and Al in equal molar ratios are added. 3+ 、Ti 4+ 、Ce 4+ The salt is dispersed in ethanol and stirred evenly to form a slurry; the slurry is spray-dried to obtain a precursor mixture; the precursor mixture is placed in a muffle furnace and heat-treated in an air atmosphere at 800° C. for 15 hours to obtain the layered oxide Na(FeMnNiAlTiCe) 1 / 6 O2.
[0038] The structure of the layered oxide is as follows: Fe, Mn, Ni, Al, Ti, Ce form an octahedral structure with the six nearest oxygen atoms, and are arranged side by side to form a transition metal layer. + It occupies an octahedral position between every two transition metal layers.
[0039] Example 4 The difference from Example 1 is that the preparation method of the layered oxide is a sol-gel method.
[0040] An O3 phase iron-manganese-nickel based high entropy sodium electric layered oxide, the general chemical formula is: Na(FeMnNiAlTiV) 1 / 6 O2.
[0041] The preparation method of the layered oxide adopts a sol-gel method, which is specifically as follows: The required sodium stoichiometric amount of 108 wt% sodium nitrate and equimolar ratios of sulfates containing nickel, manganese, iron and Al 3+ 、V 3+ 、Ti 4+ The salt is dissolved in ethanol to form a precursor solution; the solution is stirred at 100°C, and an appropriate amount of chelating agent citric acid is added, and the solution is evaporated to dryness to form a precursor gel; the precursor gel is placed in a crucible, and pre-calcined for 2 hours in an air atmosphere at 400°C; the precursor is heat-treated at 1000°C for 2 hours; the heat-treated precursor powder is ground to obtain the layered oxide Na(FeMnNiAlTiV) 1 / 6 O2.
[0042] The structure of the layered oxide is: Fe, Mn, Ni, Al, Ti, V and the six nearest oxygen atoms form an octahedral structure and are arranged side by side to form a transition metal layer. + It occupies an octahedral position between every two transition metal layers.
[0043] Example 5 The difference from Example 1 is that the chemical formula of the layered oxide is: Na(FeMnNiZrCeSn) 1 / 6 O2.
[0044] An O3 phase iron-manganese-nickel based high entropy sodium layered oxide with the general chemical formula: Na(FeMnNiZrCeSn) 1 / 6 O2.
[0045] The preparation method of the layered oxide adopts a spray drying method, which is specifically as follows: Sodium acetate containing 105 wt% of the required sodium stoichiometry and nitrates containing nickel, manganese, iron and Zr in equal molar ratios were added. 4+ 、Ce 4+ Sn4+ The salt is dispersed in ethanol and stirred evenly to form a slurry; the slurry is spray-dried to obtain a precursor mixture; the precursor mixture is placed in a muffle furnace and heat-treated in an air atmosphere at 800° C. for 15 hours to obtain the layered oxide Na(FeMnNiZrCeSn) 1 / 6 O2.
[0046] The structure of the layered oxide is: Fe, Mn, Ni, Zr, Ce, Sn respectively form an octahedral structure with the six nearest oxygen atoms, and are arranged side by side to form a transition metal layer, and the alkali metal ion Na + It occupies an octahedral position between every two transition metal layers.
[0047] Example 6 An O3 phase iron-manganese-nickel based high entropy sodium layered oxide with the general chemical formula: Na(FeMnNiAlZrCe) 1 / 6 O2.
[0048] The preparation method of the layered oxide adopts a sol-gel method, which is specifically as follows: The required sodium stoichiometric amount of 102 wt% sodium acetate and nitrates containing nickel, manganese, iron and Al in equal molar ratios are added. 3+ 、Zr 4+ 、Ce 4+ The salt is dissolved in water to form a precursor solution; the solution is stirred at 50°C, and an appropriate amount of chelating agent citric acid is added, and the solution is evaporated to dryness to form a precursor gel; the precursor gel is placed in a crucible, and pre-calcined for 2 hours in an air atmosphere at 200°C; the solution is heat-treated at 600°C for 24 hours; the heat-treated precursor powder is ground to obtain the layered oxide.
[0049] The structure of the layered oxide is as follows: Fe, Mn, Ni, Al, Zr, and Ce form an octahedral structure with the six nearest oxygen atoms, and are arranged side by side to form a transition metal layer. + It occupies an octahedral position between every two transition metal layers.
[0050] Example 7 An O3 phase iron-manganese-nickel based high entropy sodium electric layered oxide, the general chemical formula is: Na(FeMnNiVCeSn) 1 / 6 O2.
[0051] The preparation method of the layered oxide adopts a sol-gel method, which is specifically as follows: The required sodium stoichiometric amount of 108 wt% sodium nitrate and equimolar ratios of sulfates containing nickel, manganese, iron and Al 3+ 、V 3+ 、Ti 4+The salt is dissolved in ethanol to form a precursor solution; the solution is stirred at 100°C, and an appropriate amount of chelating agent citric acid is added, and the solution is evaporated to dryness to form a precursor gel; the precursor gel is placed in a crucible, and pre-calcined for 2 hours in an air atmosphere at 400°C; the precursor is heat-treated at 1000°C for 2 hours; the heat-treated precursor powder is ground to obtain the layered oxide Na(FeMnNiAlTiV) 1 / 6 O2.
[0052] A mixture of 105 wt% of the required sodium stoichiometry of sodium carbonate and sodium sulfate, and 105 wt% of the required sodium nitrate and 10 wt% of the required sodium nitrate. 3+ 、Ce 4+ Sn 4+ The salt is dissolved in ethanol to form a precursor solution; the solution is stirred at 80°C, and an appropriate amount of chelating agent citric acid is added, and the solution is evaporated to dryness to form a precursor gel; the precursor gel is placed in a crucible, and pre-calcined for 2 hours in an air atmosphere at 300°C; the solution is heat-treated at 8000°C for 10 hours; the heat-treated precursor powder is ground to obtain the layered oxide.
[0053] The structure of the layered oxide is as follows: Fe, Mn, Ni, V, Ce, Sn form an octahedral structure with the six nearest oxygen atoms, and are arranged side by side to form a transition metal layer. + It occupies an octahedral position between every two transition metal layers.
[0054] Example 8 An O3 phase iron-manganese-nickel based high entropy sodium layered oxide with the general chemical formula: Na(FeMnNiTiZrSn) 1 / 6 O2.
[0055] The preparation method of the layered oxide adopts a sol-gel method, which is specifically as follows: The required sodium sulphate is 106 wt% sodium sulfate, and sulphates containing nickel, manganese, iron and Ti in equal molar ratios. 4+ 、Zr 4+ Sn 4+ The salt is dissolved in ethanol to form a precursor solution; the solution is stirred at 100°C, and an appropriate amount of chelating agent citric acid is added, and the solution is evaporated to dryness to form a precursor gel; the precursor gel is placed in a crucible, and pre-calcined for 2 hours in an air atmosphere at 500°C; the precursor is heat-treated at 700°C for 12 hours; the heat-treated precursor powder is ground to obtain the layered oxide Na(FeMnNiTiZrSn) 1 / 6 O2.
[0056] The structure of the layered oxide is as follows: Fe, Mn, Ni, Ti, Zr, Sn form an octahedral structure with the six nearest oxygen atoms, and are arranged side by side to form a transition metal layer. + It occupies an octahedral position between every two transition metal layers.
[0057] Example 9 An O3 phase iron-manganese-nickel based high entropy sodium layered oxide with the general chemical formula: Na(FeMnNiAlTiSn) 1 / 6 O2.
[0058] The preparation method of the layered oxide adopts a sol-gel method, which is specifically as follows: The required sodium stoichiometric amount of 108 wt% sodium nitrate and equimolar ratios of sulfates containing nickel, manganese, iron and Al 3+ 、Ti 4+ Sn 4+ The salt is dissolved in ethanol to form a precursor solution; stirred at 100°C, and an appropriate amount of chelating agent citric acid is added, and evaporated to form a precursor gel; the precursor gel is placed in a crucible, pre-calcined for 2 hours in an air atmosphere at 400°C; and then heat-treated at 1000°C for 2 hours; the heat-treated precursor powder is ground to obtain the layered oxide Na(MnNiFeAlTiSn) 1 / 6 O2.
[0059] The structure of the layered oxide is: Fe, Mn, Ni, Al, Ti, Sn respectively form an octahedral structure with the six nearest oxygen atoms, and are arranged side by side to form a transition metal layer, and the alkali metal ion Na + It occupies an octahedral position between every two transition metal layers.
[0060] Comparative Example 1 The difference from Example 1 is that the chemical formula of the layered oxide is: Na(FeMnNiCoTiCu) 1 / 6 O2.
[0061] A layered oxide with the general chemical formula: Na(FeMnNiCoTiCu) 1 / 6 O2.
[0062] The preparation method of the layered oxide adopts a spray drying method, which is specifically as follows: The required sodium stoichiometric amount of 105 wt% sodium acetate and nitrates containing nickel, manganese, iron and Co in equal molar ratios were added. 3+ 、Ti 4+ , Cu 2+The salt is dispersed in ethanol and stirred evenly to form a slurry; the slurry is spray-dried to obtain a precursor mixture; the precursor mixture is placed in a muffle furnace and heat-treated in an air atmosphere at 800° C. for 15 hours to obtain the layered oxide Na(FeMnNiCoTiCu) 1 / 6 O2.
[0063] Application Example 1 The layered oxide Na(FeMnNiAlTiV) prepared in Example 1 1 / 6 O2 is used as a positive electrode material and is used in the preparation of positive electrode sheets.
[0064] A positive electrode sheet, comprising: a current collector aluminum foil, a conductive additive carbon black coated on the current collector, a binder polyvinylidene fluoride and the positive electrode material layered oxide Na (FeMnNiAlTiV) 1 / 6 O2. It is used in the preparation of sodium ion batteries.
[0065] Performance Characterization The layered oxides prepared in the above-mentioned embodiments and comparative examples were used as working electrodes to carry out performance tests.
[0066] The specific test method is as follows: The battery is assembled in a glove box with an Ar atmosphere. A metal sodium sheet is used as the counter electrode, and a 1M NaPF6 ethylene carbonate (EC): diethyl carbonate (DEC) solution is used as the electrolyte to assemble the battery for charge and discharge tests. The discharge cut-off voltage is 2.0V, the charge cut-off voltage is 4.2V, and the tests are carried out at current densities of 1 / 3C, 2C, and 3C, respectively. The measured electrochemical properties of the material are shown in the table below.
[0067] Table 1. 1 / 3C, 2C, 3C gram capacity values of Examples 1-3 and Comparative Example 1 sample XYZ 1 / 3C gram capacity 2C Gram Capacity 3C Gram Capacity Example 1 AlTiV 115.08mAh / g 93.63mAh / g 74.41mAh / g Example 2 AlTiV 114.97mAh / g 91.89mAh / g 73.64mAh / g Example 3 AlTiCe 112.52mAh / g 89.34mAh / g 66.17mAh / g Comparative Example 1 CoTiCu 110.43mAh / g 87.52mAh / g 63.31mAh / g It can be seen from the 1 / 3C, 2C, and 3C gram capacity values of Examples 1-3 and Comparative Example 1 in the above table that the layered oxide prepared in the present invention has the advantages of high rate and low impedance when used as an electrode material; compared with the comparative example, the 1 / 3C gram capacity value of each embodiment has an advantage, and the retention rates of 2C gram capacity and 3C gram capacity are also higher than those of the comparative example, that is, the gram capacity decay is reduced.
[0068] Compared with the comparative example 1, the difference between the embodiment 1 and the comparative example 1 is that Na(FeMnNiXYZ) 1 / 6The X and Z elements in O2 are different. The XYZ in Example 1 is AlTiV, and the XYZ in Comparative Example 1 is CoTiCu. Because the content of transition metal elements is high, the gram capacity is not as good as that in Example 1. It can be seen that only in the combination of metal ions of the present invention can better effects be achieved. The reasons are analyzed as follows: In the layered oxide prepared by the present invention, the introduction of Al helps to form Ni-Al bonds, thereby enhancing the orbital bonding of Al-O bonds, inhibiting oxidation reactions, and greatly improving the structural stability and safety of the positive electrode material; in addition, it can also inhibit the pulverization of secondary particles and enhance the intermediate phase of the electrode / electrolyte, thereby improving the rate capability and cycle performance at room temperature and high temperature. It can be seen that the several metal ions of the present invention cooperate with each other to achieve better experimental results.
[0069] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. An O3 phase iron-manganese-nickel based high entropy sodium electric layered oxide, characterized in that: The general chemical formula is: Na(FeMnNiXYZ) 1 / 6 O2, X, Y and Z are Al 3+ 、V 3+ 、Ti 4+ , Zr 4+ 、Ce 4+ Sn 4+ Three of them.
2. The O3-phase iron-manganese-nickel-based high-entropy sodium-electrolyte layered oxide according to claim 1, characterized in that: The structure of the layered oxide is as follows: Fe, Mn, Ni, X, Y and Z form an octahedral structure with the six nearest oxygen atoms, and are arranged side by side to form a transition metal layer. + It occupies an octahedral position between every two transition metal layers.
3. A method for preparing the O3 phase iron-manganese-nickel based high entropy sodium electric layered oxide according to any one of claims 1-2, characterized in that: The method is a solid phase method, comprising the following steps: mixing sodium salt and oxides of Fe, Mn, Ni, X, Y and Z in proportion to form a precursor; heat treating at 800 to 1000°C for 10 to 24 hours after mixing; and obtaining the layered oxide.
4. A method for preparing the O3 phase iron-manganese-nickel based high entropy sodium electric layered oxide according to any one of claims 1-2, characterized in that: The method is a sol-gel method, comprising the following steps: dispersing sodium salt and nitrate or sulfate containing nickel, manganese, iron and salt of XYZ in a solvent to obtain slurry; stirring at 50-100°C, adding an appropriate amount of chelating agent, and evaporating to form a precursor gel; pre-calcining the precursor gel at 200-500°C for 2-3 hours; and then heat treating at 600-1000°C for 2-24 hours; grinding the heat-treated precursor powder to obtain the layered oxide.
5. A method for preparing the O3 phase iron-manganese-nickel based high entropy sodium electric layered oxide according to any one of claims 1-2, characterized in that: The method is a spray drying method, comprising the following steps: dispersing sodium salt and nitrate or sulfate containing nickel, manganese, iron and salt of XYZ in an equal molar ratio in a solvent and stirring them evenly to form a slurry; spray drying the slurry to obtain a precursor mixture; heat treating the precursor mixture in an air atmosphere at 700 to 1000° C. for 10 to 24 hours to obtain the layered oxide.
6. An application of the O3 phase iron-manganese-nickel based high entropy sodium electric layered oxide according to any one of claims 1-2, characterized in that: Used as positive electrode material.
7. A positive electrode sheet, characterized in that: Comprising the positive electrode material as claimed in claim 6.
8. A positive electrode sheet according to claim 7, characterized in that: The invention also includes a current collector, a conductive additive coated on the current collector, and a binder.
9. A positive electrode sheet according to claim 8, characterized in that: The conductive additive includes: one or more of carbon black, graphite powder, carbon nanotubes, and graphene; the binder includes: a solution of one or more of polyvinylidene fluoride PVDF, polytetrafluoroethylene PTFE, sodium alginate, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR; the current collector includes: one of aluminum foil, nickel mesh, titanium mesh, stainless steel mesh, and nickel foam.
10. A sodium ion battery, characterized in that: Including the positive electrode sheet as described in claim 7.
Citation Information
Patent Citations
A sodium-rich P2 phase layered oxide material, its preparation method and applications
CN104795560B
A layered O3 phase nickel oxide cathode material, its preparation method and applications
CN104795561B
Sodium-magnesium-iron-manganese-based layered oxide material as well as preparation method and application thereof
CN113078298A